Effects of 2 Forms of Practice Facilitation on Cardiovascular Prevention in Primary Care: A Practice-randomized, Comparative Effectiveness Trial. Issue 4 (April 2020) - Persell, Stephen D.; Liss, David T.; Walunas, Theresa L.; Ciolino, Jody D.; Ahmad, Faraz S.; Brown, Tiffany; French, Dustin D.; Hountz, Randy; Iversen, Karen; Lindau, Stacy T.; Lipiszko, Dawid; Makelarski, Jennifer A.; et al.
Abstract : Background: Effective quality improvement (QI) strategies are needed for small practices. Objective: The objective of this study was to compare practice facilitation implementing point-of-care (POC) QI strategies alone versus facilitation implementing point-of-care plus population management (POC+PM) strategies on preventive cardiovascular care. Design: Two arm, practice-randomized, comparative effectiveness study. Participants: Small and mid-sized primary care practices. Interventions: Practices worked with facilitators on QI for 12 months to implement POC or POC+PM strategies. Measures: Proportion of eligible patients in a practice meeting "ABCS" measures: (Aspirin) Aspirin/antiplatelet therapy for ischemic vascular disease, (Blood pressure) Controlling High Blood Pressure, (Cholesterol) Statin Therapy for the Prevention and Treatment of Cardiovascular Disease, and (Smoking) Tobacco Use: Screening and Cessation Intervention, and the Change Process Capability Questionnaire. Measurements were performed at baseline, 12, and 18 months. Results: A total of 226 practices were randomized, 179 contributed follow-up data. The mean proportion of patients meeting each performance measure was greater at 12 months compared with baseline: Aspirin 0.04 (95% confidence interval: 0.02–0.06), Blood pressure 0.04 (0.02–0.06), Cholesterol 0.05 (0.03–0.07), Smoking 0.05 (0.02–0.07); P <0.001 for each. Improvements were sustained at 18 months. At 12 months, baseline-adjusted difference-in-differences in proportions for the POC+PM arm versus POC was: Aspirin 0.02 (−0.02 to 0.05), Blood pressure −0.01 (−0.04 to 0.03), Cholesterol 0.03 (0.00–0.07), and Smoking 0.02 (−0.02 to 0.06); P >0.05 for all. Change Process Capability Questionnaire improved slightly, mean change 0.30 (0.09–0.51) but did not significantly differ across arms. Conclusion: Facilitator-led QI promoting population management approaches plus POC improvement strategies was not clearly superior to POC strategies alone. Abstract : Supplemental Digital Content is available in the text.